Preference of School Mathematics and its Link to External Evaluation and Self-evalutaion - Smetáčková, Irena (Scientia in educatione, 2018)
The popularity of math as a school subject is a crucial factor fostering educational motivation and student performance in the subject. This paper seeks to answer the question as to whether the popularity of math is related to either external evaluation (final math exam assessment and the student’s achievement in a didactic test) or internal self-evaluation (the student’s confidence in his or her math competence and mathematical self-efficacy). The study examined a total of 1 383 students, spanning 4th through 9th grades of grammar school, who answered the questionnaire and took the mathematical test. The analysis showed that math popularity was decreasing across age groups — older students preferred math significantly less than younger students; and also with regard to gender, as female students preferred math significantly less than male students. Moreover, it showed that the low math popularity was statistically connected to a worse grade, worse test results, the student’s weaker confidence in his or her math competence, and also weaker math selfefficacy. The external evaluation (test results and the final assessment on the student’s report card) had a significantly lower predictor function than internal self-evaluation.